IMPACT OF CELEBRITY ENDORSEMENT ON BRAND EQUITY - Ibne-Ali Jaffari, Seyed; Ahmad, Farooq; Mehtab, Muhammad; Iqbal, Asif (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This research intends to explore the empirical relationship between endorsers credibility and consumer based brand equity in the presence of mediating role of brand credibility and moderating role of type of celebrities i.e. National or International was also examined. This paper uses two theories to explain the relationship; associative learning was used to explain the relationship between endorser and brand equity, and brand signaling to explain the relationship about the mediating role of brand credibility. The data was collected from Islamabad, the Federal capital of Pakistan and analyzed using SPSS. Results suggest that endorsers credibility has positive impact on brand equity and brand credibility mediates this relationship. The moderating role of type of celebrity was also discussed in this paper. The past literature suggests that celebrity endorser is one who is perceived as attractive, expert and trustworthiness. This research study examined the relationship of construct in the context of non-durable goods and measured the effectiveness of celebrity i.e. National or International proved to build brand equity.